INTERPRETATION OF TRI (3) PROVIDER “BEBAS ITU NYATA ALWAYS ON” SLOGAN BY T HE USERS IN ENGLISH DEPARTMENT OF FACULTY OF CULTURAL STUDIES AT UNIVERSITAS BRAWIJAYA - NUHA, MUHAMMAD ULIN (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Critical Discourse Analysis, Slogan, Tri (3) Provider This research is about the analysis of critical discourse analysis in slogan“Bebas itu nyata always on” used by Tri provider by using Fairclough model ofCDA. There are three objectives in to achieve this research, first is to find out thelexical and structural meanings of Tri provider slogan of “Bebas itu nyata alwayson”, the second one is to identify the users’ interpretation of Tri provider inEnglish Department at Universitas Brawijaya toward the slogan of “Bebas itunyata always on”, and the last one is identify the impact of Tri slogan “Bebas itunyata always on” toward the users in English Department at UniversitasBrawijaya.This study used a qualitative approach to analyze two data. The first datumis the slogan text “Bebas Itu Nyata Always On” used in Tri (3) provider. Thesecond one is the opinion about the product produced by the students of Englishdepartment at Universitas Brawijaya. There are two data collections, namely preresearch and whilst research. In addition the researcher also needs othersinstruments such as questionnaire and interview guide to conduct the research. In data analysis, the researcher uses two processes such as analyzing the sentence of the slogan text and analyzing the result of interviewed.The result of this research revealed that semantically the slogan has good lexical choice since it emphasizes the words Bebas, Nyata, and always on to persuade the audiences.Furthermore, sintagmaticlly the slogan consists of twosentences, the first sentence is Bebas yang diberikan Tri itu nyata and the second one is we are always on. At the level of interpretation, there are similarities between the research participants and the researcher in interpreting the slogan. Besides, slogan has less power to influence the users or researcher participants in buying a certain product.In conclusion, the power of language in advertisement is very importantsince it has the function to persuade people in buying a certain product, in fact in this research the researcher found that language has less power in influencingpeople to choose a certain product, people choose a certain product since theproduct has good quality of services. For further research, the researchersuggested for the next researcher to apply more theories in CDA such as analyzing the coherence or cohesive in the text analysis so that it will be helpful for the readers to understand more about the theory of CDA.